Knowledge and Practice of Traffic Rules and Regulations among Secondary Level Students (SNPRC Journal, 2024)
Road traffic accidents (RTAs) are a leading cause of injury and mortality among adolescents, especially in rapidly urbanizing areas like Butwal Sub-Metropolitan City, Nepal. This study aimed to assess the knowledge and practice of traffic rules and regulations among higher secondary students. A cross-sectional survey design was employed, with a sample of 255 students selected through proportional stratified random sampling from four secondary schools. Data were collected using a structured questionnaire and analyzed using SPSS version 25. The findings revealed that while a majority of students demonstrated good theoretical knowledge for example, 94.5 percent understood traffic light signals, practical adherence was inconsistent. Only 61.2 percent of respondents stated never wearing seat belts when traveling in four-wheelers, indicating a gap between knowledge and practice. Statistical analysis showed a significant association between gender and knowledge of traffic rules, though no significant difference was found between boys and girls regarding their road safety practices. The study highlights the crucial need for school based traffic education programs that not only impart knowledge but also promote behavioral change through experiential learning. Consolidation road safety awareness at the secondary level could contribute to reducing adolescent involvement in RTAs and improving community traffic safety overall.